Mommy Urtula ; Philippine Olympic Committee ; The right to censor [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Features the national artist for dance. Lucresia Urtual ; the improper handling of delegation to the Seoul Olympics by PDC; and the MTRCB in its movie and TV reviews.